Mediator of social intermediation and financial services access - kamukama, Nixon; Bazinzi, Natamba (Emerald, 2014)
The paper examined the mediating effect of social capital in the relationship between social intermediation and financial services in Ugandan micro finance industry. The purpose of this paper is to establish the role of social capital in the relationship between social intermediation and financial services access.
Keywords: Social intermediation, Social capital, Microfinance industry, Mediating effect, Financial services access, Financial services, Uganda